Spatiotemporal gait compensations following medial collateral ligament and medial meniscus injury in the rat: correlating gait patterns to joint damage. Issue 1 (December 2015) - Kloefkorn, Heidi; Jacobs, Brittany; Loye, Ayomiposi; Allen, Kyle
Abstract Introduction After transection of the medial collateral ligament and medial meniscus (MCLT + MMT) in the rat, focal cartilage lesions develop over 4–6 weeks; however, sham surgery (MCLT alone) does not result in cartilage damage over a similar period. Thus, comparison of MCLT + MMT with the MCLT sham group offers an opportunity to investigate behavioral modifications related to focal cartilage and meniscus damage in the rat. Methods MCLT or MCLT + MMT surgery was performed in the right knees of male Lewis rats, with spatiotemporal gait patterns and hind limb sensitivity assessed at 1, 2, 4, and 6 weeks postsurgery (n = 8 rats per group per time point, n = 64 total). After the animals were euthanized, Histology was performed to assess joint damage. Results MCLT + MMT animals had unilateral gait compensations at early time points, but by week 6 bilateral gait compensations had developed in both the MCLT sham and MCLT + MMT groups. Conversely, heightened tactile sensitivity was detected in both MCLT sham and MCLT + MMT animals at week 1, but only the MCLT + MMT animals maintained heightened sensitivity to week 6. Cartilage lesions were found in the MCLT + MMT group but not in the MCLT sham group. Correlations could be identified between joint damage and gait changes in MCLT + MMT animals; however, the same gait changes were found with MCLT sham animals despite a lack of joint damage. Conclusions Combined, our data highlight a common conundrum in osteoarthritis (OA) research: Some behavioral changes correlate to cartilage damage in the OA group, but the same changes can be identified in non-OA controls. Of the behavioral changes detected, allodynia was maintained in MCLT + MMT animals but not in the MCLT sham group. However, the correlation between cartilage damage and hind limb sensitivity is relatively weak (R = −0.4498), and the range of sensitivity measures overlaps between groups. The factors driving gait abnormalities in MCLT and MCLT + MMT animals also remain uncertain. The gait modifications are similar between groups and do not appear until weeks after surgery, despite cartilage damage being focused in the MCLT + MMT group. Combined, our data highlight the need to evaluate the links between noncartilage changes and behavioral changes following joint injury in the rat.